(untitled) (Journal of Environmental Bioremediation and Toxicology, 2013)
The development of an inhibitive assay for lead using a molybdenum-reducing enzyme assay system is presented for the first time. The assay is based on the ability of lead to inhibit the molybdenum-reducing enzyme of a bacterium. The Â molybdenum-reducing enzyme was assayed using 12-molybdophosphoric acid at pH 5.0 as an electron acceptor substrate and NADH as the electron donor substrate. The enzyme in the crude extract converted the yellowish solution into a deep blue solution with a maximum peak at 865 nm and a shoulder at 710 nm. Lead exhibited a sigmoidal inhibition curve. The calculated IC50 using the four-parameter logistic model for lead was 2.186 mg l-1 and the regression coefficient was 0.998. The limit of detection (LOD) for lead was 0.021 mg l-1 while the limit of quantitation (LOQ) for leady was 0.237 mg l-1, respectively. The comparative LC50, EC50 and IC50 data for lead in different toxicity tests show that the IC50 value for lead was higher than Ulva pertussae, lower than the value for immobilised urease, Daphnia magna, and rainbow trout and within the range of the papain assay.